SURVEI NYAMUK Anopheles spp DI PESISIR SELAT LEMBEH KOTA BITUNG - Kojongian, Geibs; Pijoh, Victor D; Bernadus, Janno B B (JKK (Jurnal Kedokteran Klinik), 2016)
ABSTRACT : Development in transportation sector accelerate the transfer and spreading of mosquito species and pathogen that causing mosquito-borne diseases. Anopheles mosquito is one of the main vector, mainly malaria. In Indonesia malaria is almost found in some places. Bitung city is one of the endemic area in North Sulawesi which in 2016 are reported 27 new cases. Bitung city known as city of harbor which supports the spreading of malaria disease that originate from other area. The mangrove which located at Lembeh island become the location of growth from Anopheles mosquito. Aim: to know the description of Anopheles mosquito at coastal of bay Lembeh, Bitung City. Methods: using descriptive methods with cross-sectional design. Mosquitoes in location of this research are being captured and identified using identification key at Parasitology Laboratory Medical Faculty of Sam Ratulangi Universty. Result: based on the research result there are found no Anopheles mosquito, Culex dominated the result of captured, counted at 205 mosquitoes and Aedes counted 76 mosquitoes. Conclusion: there are no Anopheles mosquitoes were found at coastal of bay Lembeh, Bitung City. Keywords: Anopheles, coastal of bay Lembeh Abstrak: Perkembangan dalam bidang transportasi mempercepat perpindahan dan penyebaran jenis nyamuk dan patogen yang menyebabkan penyakit bersumber nyamuk (PBN). Nyamuk Anopheles merupakan salah satu penular penyakit terutama malaria. Di Indonesia malaria masih ditemukan hampir di seluruh provinsi. Kota Bitung merupakan salah satu daerah endemis malaria di Sulawesi Utara yang pada tahun 2016 dilaporkan 27 kasus baru. Kota Bitung sebagai kota pelabuhan mendukung penyebaran penyakit malaria dari daerah lain. Hutan mangrove yang ada di pulau Lembeh menjadi tempat perkembangbiakan nyamuk Anopheles. Tujuan penelitian: Untuk mengetahui gambaran nyamuk Anopheles di pesisir selat Lembeh Kota Bitung. Metode penelitian : deskriptif dengan pendekatan potong lintang. Nyamuk yang ada di lokasi penelitian ditangkap dan diidentifikasi menggunakan kunci identifikasi di Laboratorium Parasitologi Fakultas Kedokteran Universitas Sam Ratulangi. Hasil Penelitian: Berdasarkan hasil penelitian tidak ditemukan nyamuk Anopheles, nyamuk Culex mendominasi hasil tangkapan sebanyak 205 ekor dan Aedes berjumlah 76 ekor. Kesimpulan: Tidak ditemukan nyamuk Anopheles di pesisir selat Lembeh Kota Bitung. Kata kunci: Anopheles, pesisir selat Lembeh